Perbedaan Jumlah Lalat Tertangkap Sticky Trap Antara Menggunakan Umpan Ekstrak Buah Durian Dengan Umpan Ekstrak Kayu Manis - Yayan Wijayanti; Winarko .; Pratiwi Hermiyanti (Poltekkes Kemenkes Surabaya, 2015)
Given the fact that flies are attracted by strong odors, flies controlling can be carried out by using scent lure trap. However, flies’ most preferred scent has not been known. This study aimsto determine difference in the number of flies caught on sticky traps between using lures of durianfruit extract and cinnamon extract lure. Durian fruit extracts contains alcohol while cinnamon contains eugenol.This is a quasi-experimental design research with Only Control Group Design Post-Test. This research was conducted in TPS of Bukit Barisan. This study covers the extraction with alcohol solvent. The extraction result was then dropped into the sticky trap and subsequently used to catchflies. The results shows that there were higher average number of flies caught on sticky trap ofcinnamon extract lure with 12-21 flies / trap than those in durian fruit extract trap which were only 10-14 flies / trap. The results of the data analysis by T test shows that there were difference in thenumber of flies caught on sticky traps between using lures of durian fruit extract and cinnamon extract (P = 0.033 0.05)It is advisable to use physical ways of using sticky traps with durian fruit or cinnamon . In addition to their safety and environmentally friendly, they are proven to reduce flies population.